Predictors of nursing leadership in Uganda: a cross-sectional study. (9th November 2020) - Nanyonga, Rose Clarke; Bosire, Edna N; Heller, David J; Bradley, Elizabeth; Reynolds, Nancy R
Abstract: Evidence regarding the role of nurses-in-leadership and how to engage nurses in policy decisions is minimal in sub-Saharan Africa. The purpose of this study was: (1) to assess the leadership practices of nurses-in-leadership in Uganda (by self-report) and from the perspective of 'followers' (direct-report, peers, co-workers, other); and (2) to determine factors (positively) associated with leadership practices. We surveyed 480 nurses, 120 in leadership roles ( Response Rate 57%) and 360 'followers' ( Response Rate 60%), who were recruited from five hospitals in Kampala, Uganda. We used the Leadership Practice Inventory (Self and Observer), a project-specific demographic questionnaire and Denison's Organizational Culture Survey (DOCS). Sixty-three per cent of the respondents held a registered nursing certificate; 79% had received formal leadership training; 47% were based in private for-profit (PFP) hospitals, 28% in private not-for-profit (PNFP) and 25% in public hospitals. Among the five leadership practices, nurses-in-leadership used the practice of Model the Way (M  =  8.27, SD  =  1.30), C hallenge the Process (M  =  8.12, SD  =  1.30) and Encourage the Heart (M  =  8.04, SD  =  1.51) more frequently (on a 10-point Likert Scale). Inspire a Shared Vision (M  =  7.82, SD  =  1.57) and Enable Others to Act (M  =  7.62, SD  =  1.66) practices were used less frequently . The same rank order was true for leadership scores from the perception of followers. However, leadership scores by followers were significantly lower ( P  <   0.01) than the nurse leader self-reported scores across all sub-scales. Leadership practice scores were higher in public than private hospitals ( P  <   0.0001). Organizational culture (OC) was associated ( P  <   0.001) with leadership practices. Although overall leadership practice scores were generally high, the less frequent use of Inspire and Enable practices suggests opportunities for targeted improvement. Moreover, differences between self-reported and leadership scores by followers suggest perception gaps between leaders and their followers. The positive relationship between public hospital settings and self-reported leadership practices among nurses-in-leadership suggests that important nursing leadership practices are possible even in a low-resource clinical setting.